Removal of ammonia nitrogen from copper-loaded resin based on ligand adsorption. Issue 1 (January 2021) - Chen, Quanzhou; Si, Wantong; Liu, Jumei; Ge, Xiaoxi; Yang, Jun
Abstract: A ligand adsorbent with strong selectivity towards ammonia nitrogen in solution was prepared by loading Cu onto the chelating resin of iminediacetic acid. The static adsorption results showed that the removal rate of ammonia nitrogen reached the maximum when the equilibrium pH of solution was 9.5-10. The presence of competing cations, such as Na + and Ca 2+, had no obvious effect on the optimal equilibrium pH, but had a certain inhibitory effect on the adsorption of ammonia nitrogen and Ca 2+ > Na + . The adsorption of ammonia nitrogen by copper-loaded resin was in line with the Langmuir isothermal equation, and the maximum adsorption capacity of ammonia nitrogen was 44mg/g(dried copper-loaded resin).